Treatment of difficult-to-treat depression – clinical guideline for selected interventions. (1st April 2022) - Moeller, Stine Bjerrum; Gbyl, Krzysztof; Hjorthøj, Carsten; Andreasen, Maike; Austin, Stephen F.; Buchholtz, Poul Erik; Fønss, Line; Hjerrild, Simon; Hogervorst, Lise; Jørgensen, Martin Balslev; Ladegaard, Nicolai; Martiny, Klaus; et al.
Abstract: Background: Difficult-to-treat-depression (DTD) is a clinical challenge. The interventions that are well-established for DTD are not suitable or effective for all the patients. Therefore, more treatment options are highly warranted. We formulated an evidence-based guideline concerning six interventions not well-established for DTD in Denmark. Methods: Selected review questions were formulated according to the PICO principle with specific definitions of the patient population (P), the intervention (I), the comparison (C), and the outcomes of interest (O), and systematic literature searches were performed stepwise for each review question to identify relevant systematic reviews/meta-analyses, and randomized controlled trials. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was used to assess the methodological quality of the included studies. Clinical recommendations were formulated based on the evidence, the risk-benefit ratio, and perceived patient preferences. Results: We found sufficient evidence for a weak recommendation of repetitive transcranial magnetic stimulation (rTMS) and cognitive behavioural analysis system of psychotherapy (CBASP). The use of bright light therapy in DTD was not sufficiently supported by the evidence, but should be considered as good clinical practice. The interventions should be considered in addition to ongoing antidepressant treatment. We did not find sufficient evidence to recommend intravenous ketamine/esketamine, rumination-focused psychotherapy, or cognitive remediation to patients with DTD. Conclusion: The evidence supported two of the six reviewed interventions, however it was generally weak which emphasizes the need for more good quality studies. This guideline does not cover all treatment options and should be regarded as a supplement to relevant DTD-guidelines.